HYDROPONIC VEGETABLE SUPPLY CHAIN ANALYSIS (CASE STUDY OF MODERN MARKET DIAN PERTIWI POKA AMBON CITY) - Fitriani Suyono; Natelda R. Timisela; Maisie T. F. Tuhumury (JURNAL AGRICA, 2023)
Hydroponic vegetables are horticultural commodities that are very important to meet the nutritional needs of the community. The increase in population also contributes to the increase in demand for horticultural commodities. One of the vegetable commodities produced is hydroponic vegetables. The increasing demand for hydroponic vegetables has led to the emergence of hydroponic entrepreneurs who have begun to develop hydroponic vegetable commodities, but problems with meeting demand arise due to the limited supply of hydroponic vegetables. This study aims to determine the supply chain of hydroponic vegetables in the modern market of Dian Pertiwi Poka, Ambon City and to determine marketing margins and marketing efficiency in the supply chain. The data collected in this study are primary data and secondary data. The results of this study indicate that the supply chain of hydroponic vegetables in the Dian Pertiwi supermarket through the supply chain, namely: Dian Pertiwi supermarket → consumers. Based on the marketing analysis of lettuce hydroponic vegetables and pakcoy the marketing margin on the hydroponic lettuce supply chain is Rp. 14,985 and pakcoy Rp. 14,250. The most efficient marketing is the marketing of pakcoy vegetables with an efficiency value of 19.04 percent